2013
DOI: 10.4103/0970-9290.116682
|View full text |Cite
|
Sign up to set email alerts
|

Topography of the pulp chamber in the maxillary primary molars of a Tunisian children

Abstract: Mesiodistal dimension of the pulp cavity is not proportional to that of the dental crown. Endodontic access cavity have to be shifted to the distal and vestibular sides from the first to the second upper molar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…13 However, Godze Oscan has found four classes (class I–IV) in the root canal of primary molars. 14 , 15 But in our study, apart from the four classes (class I–IV), we found one more variant which has not been much reported in the literature. As a result, this research suggests that CBCT is useful in evaluating the root and canal system, but it should not be utilized routinely.…”
Section: Discussioncontrasting
confidence: 69%
“…13 However, Godze Oscan has found four classes (class I–IV) in the root canal of primary molars. 14 , 15 But in our study, apart from the four classes (class I–IV), we found one more variant which has not been much reported in the literature. As a result, this research suggests that CBCT is useful in evaluating the root and canal system, but it should not be utilized routinely.…”
Section: Discussioncontrasting
confidence: 69%
“…Nevertheless, for the analysis of biological effects, this methodological feature is irrelevant to determining the anatomical dimensions of a primary tooth; moreover, radiation in paediatric patients should be restricted to extremely necessary cases. However, the “in vitro” methodology is more rigorous in anatomical studies, such as this and other studies [ 1 , 2 , 3 , 4 , 5 , 6 , 9 , 11 , 12 , 13 , 16 , 27 , 34 , 35 , 36 ], by allowing the fixation of the teeth during handling.…”
Section: Discussionmentioning
confidence: 99%
“…This fact becomes more important in a primary tooth, as it presents a lower thickness of enamel and dentine tissues [ 4 ]. Making a correct access cavity in pulp therapy allows for the removal of all tissues housed in the chamber and correct visualisation of both the pulp floor and the entrance to the root canals, thus improving the long-term prognosis [ 5 , 6 , 7 , 8 , 9 ]. Furthermore, knowledge of the morphological characteristics of the chamber pulp floor prevents possible iatrogenesis during the technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The close approximation of ZOE material in the mesio-distal confines of the pulpal cavity must have blinded its inadequate condensation in the opposite bucco-lingual margins. Baccouche et al studied the topography of primary molars and observed that the greatest dimension of the pulp chamber was significantly higher in the buccolingual axis than mesiodistal particularly in primary maxillary molars ( Baccouche et al, 2013 ). This difference in the pulp chamber proportions can contribute to a greater number of teeth with poor ZOE condensation as seen on antero-posterior xrays in the current study.…”
Section: Discussionmentioning
confidence: 99%